El Tigre - Yearbook 1985 - Huxel, Lary; McGowen, Butch; Ward, Dan; Davis, Jim (Raton, NM Raton High School, 1985)
School yearbook for the year 1985, with people and activities done through the school year.
Dedication to the future classes
55082
Keywords: High School Yearbooks -- Raton, NM; Annuals -- Raton, NM